Is Genomic DNA extracted and stored at -20°C for long time useful in forensic field?. Issue 1 (December 2019) - Sguazzi, Giulia; Lovisolo, Flavia; Gino, Sarah
Abstract: With the progress of technologies, forensic genetic laboratories have been more frequently involved in "cold case". The aim of this study was to understand whether the DNA extracted and stored for a long time at−20 °C could be useful for new analyses in order to identify the perpetrator of unsolved crimes, especially when evidence is no longer available. We selected 120 DNA samples obtained from evidence collected at crime scene between 2001 and 2010: they were quantified again using Realtime PCR and the "Plexor HY System" kit. The results were compared with those obtained in the past. For 37 samples discrepancies were observed (i.e. positive quantification, identification of male material mixed with female ones). Then these samples were amplified with "AmpFISTR Identifiler Plus" and "PowerPlex ESI 17 Fast System" kits. Genetic profiles useful for a comparison were obtained for all the 37 analysed samples. In 5 samples mixed profiles were highlighted, unlike what was obtained in the past, and in addition, in 28 cases, where no genetic profile was previously typed, a genetic profile was also identified. The study shows how it is possible, even after a considerable time interval, to still obtain genetic profiles useful for a comparison, as well as the possibility of typing new ones. Comparing the results of the analysis of DNA polymorphisms it is possible to underline the improvement that the current techniques have brought to the typing of genetic profiles: regarding the attribution of gender and the perception of contributors within mixtures.